Flora of Ceará, Brazil: Loranthaceae - Menezes,Marcelo Oliveira Teles de (2022)
Abstract This study provides a taxonomic treatment for the species of Loranthaceae in the state of Ceará, Northeastern Brazil. The survey was made based on the previous consultation of virtual herbaria, in loco visits, material loans, and photographs of diagnostic traits sent by herbarium curators. Morphological traits and geographic coordinates of all specimens collected in the State were recorded to prepare the distribution maps, identification key, and taxonomic descriptions for each taxon. A total of 184 specimens (discounting duplicates) from 30 herbaria were studied. Eight species are recorded for Ceará: Passovia pedunculata, Passovia pyrifolia, Psittacanthus cordatus, Psittacanthus dichroos, Psittacanthus eucalyptifolius, Struthanthus marginatus, Struthanthus polyrrhizus, and Struthanthus syringifolius. None are included in the IUCN Red List. However, four of them were collected inside protected areas (i.e., Passovia pedunculata, Psittacanthus cordatus, S. polyrrhizus, and S. syringifolius).